(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of the research is the quantitative determination of macro- and microelements of the Elecampane gelenium (Inula) plant and the study of its application in medicine. For this, an autumn sample of the Andiz plant was taken, which grows in natural conditions in the Chodak MFU of the Namangan region of the Ferghana Valley. It was brought to the desired state of the sample for quantitative analysis. The results of studying the elemental composition of the plant elecampane gelenium L (Inula) by inductively coupled plasma mass spectrometry are presented. As a result of research, 44 macro- and microelements were revealed. flower and root of the plant Inula helenium L, growing in the Ferghana Valley. The results of studying the elemental composition of the plant elecampane gelenium L (Inula) by inductively coupled plasma mass spectrometry are presented. As a result of research, 44 macro- and microelements were revealed. It is shown that the amount of macroelements and microelements has a significant impact on their medicinal properties. An elemental analysis of the stem, flower and root of the Inula helenium L plant growing in the Ferghana Valley was carried out. It has been established that the roots of the Elecampane gelenium L plant contain a sufficient amount of elements of calcium, potassium, copper, iron, magnesium and phosphorus.